Perish the thought: fermentation and rot in the medieval imagination. - Nelson, Robert (Food, Culture & Society, 2025)
Although there were different words to describe fermentation and rot since archaic times, the separation of these processes is obscure. This article identifies the circumstances in which both fermentation and rot were considered either good or bad, where sometimes the understanding was informed by physiological observation and sometimes by symbolism. The article pays particular attention to a polemic that erupted on the topic of fermentation in 1053. At issue was the practice throughout the Latin church of serving an unfermented wafer for holy communion instead of sourdough. The Greeks argued that the sacrament must be baked from fermented dough to embody the warmth and life-giving quality of the Saviour's flesh, while the Latins argued that the sacrament must be unleavened bread (azyme) free of all biological chaos to reflect the purity of God. This article proposes that there is an intrinsically messy symbolism in fermentation that partly accounts for the historical contrariness. Science might have resolved some of these obscurities but others linger; and the article suggests that fermentation operates in our unconscious mind more along the lines of medieval symbolism than contemporary microbiology.